The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2164-14-418
|View full text |Cite
|
Sign up to set email alerts
|

Ambushing the ambush hypothesis: predicting and evaluating off-frame codon frequencies in Prokaryotic Genomes

Abstract: BackgroundIn this paper, we address the evidence for the Ambush Hypothesis. Proposed by Seligmann and Pollock, this hypothesis posits that there exists a selection for off-frame stop codons (OSCs) to counteract the possible deleterious effects of translational frameshifts, including the waste of resources and potential cytotoxicity. Two main types of study have been used to support the hypothesis. Some studies analyzed codon usage and showed that codons with more potential to create OSCs seem to be favored ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Furthermore, incorrectly folded mistranslated proteins may have an adverse effect on cellular interactions or form toxic aggregates ( Tank and True 2009 ). The possible evolutionary advantage of capturing these frameshifts is conjectured to be reflected by an overrepresentation of out of frame stop codons, termed the “ambush hypothesis” ( Seligmann and Pollock 2004 ; Singh and Pardasani 2009 ; Tse et al 2010 ), although the frequency with which codons that form out of frame stops are used is largely predictable from the underlying GC pressure ( Morgens et al 2013 ). Alternatively, selection to reduce costs in genomes where frameshifting is most deleterious (notably GC rich ones) can explain the richer tRNA repertoire found in such genomes ( Warnecke et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, incorrectly folded mistranslated proteins may have an adverse effect on cellular interactions or form toxic aggregates ( Tank and True 2009 ). The possible evolutionary advantage of capturing these frameshifts is conjectured to be reflected by an overrepresentation of out of frame stop codons, termed the “ambush hypothesis” ( Seligmann and Pollock 2004 ; Singh and Pardasani 2009 ; Tse et al 2010 ), although the frequency with which codons that form out of frame stops are used is largely predictable from the underlying GC pressure ( Morgens et al 2013 ). Alternatively, selection to reduce costs in genomes where frameshifting is most deleterious (notably GC rich ones) can explain the richer tRNA repertoire found in such genomes ( Warnecke et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…When a larger data set was analyzed, Morgens et al found that only a slight overexpression of PSCs in close to 2000 bacterial genomes. They also found that some out-of-frame sense codons are even more overexpressed than the PSCs[155]. Bacteria with high GC content or metabolically versatile bacteria were found to contain very few PSCs in their genome raising questions regarding the validity of the ambush hypothesis[31,155].…”
mentioning
confidence: 99%
“…For example, the polyketide synthase (PKS) genes presented with significantly lower level of hidden stop codons than expected, suggesting both non-adherence to the ambush hypothesis and a suppression of hidden stop codon evolution [8]. In addition, it was reported that some sense codons have a more significant excess than stop codons [4]. These controversial results can be well explained if the emerging of the hidden stops after the occurrence of a frameshift is considered to be a signal to trigger the cell machine for readthrough and then for reading frame recovery, rather than a signal for translational termination.…”
Section: Frameshift Tolerating and The Ambush Hypothesismentioning
confidence: 99%
“…The "Ambush Hypothesis" [3] presumed that most frameshifts would yield non-functional proteins, lead to waste of energy, resources and activity of the biosynthetic machinery, and some peptides synthesized after frameshifts were thought to be cytotoxic [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%